2017
DOI: 10.1007/s10461-017-1785-7
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Risk Prediction Algorithm for HIV Transmission: Results from HIV Prevention Trials in KwaZulu Natal, South Africa (2002–2012)

Abstract: We aimed to develop a HIV risk scoring algorithm for targeted screening among women in South Africa. We used data from five biomedical intervention trials (N = 8982 Cox regression models were used to create a risk prediction algorithm and it was internally and externally validated using standard statistical measures; 7-factors were identified as significant predictors of HIV infection: <25 years old, being single/not cohabiting, parity (<3), age at sexual debut (<16), 3+ sexual partners, using injectables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
3
27
1
Order By: Relevance
“…People with higher education level may have more access to relevant health information, presenting a broader perception on cardiovascular risk factors and the need to maintain a healthy lifestyle 22 . Singles were the majority of patients and, given this, our study showed that single people are more likely to have multiple partners, thus becoming more vulnerable to HIV 23 . However, the increase in the number of HIV infection cases among people in stable relationships must be highlighted; this derives from the lack of negotiation about condom use, especially by females 24 .…”
Section: Discussionmentioning
confidence: 58%
“…People with higher education level may have more access to relevant health information, presenting a broader perception on cardiovascular risk factors and the need to maintain a healthy lifestyle 22 . Singles were the majority of patients and, given this, our study showed that single people are more likely to have multiple partners, thus becoming more vulnerable to HIV 23 . However, the increase in the number of HIV infection cases among people in stable relationships must be highlighted; this derives from the lack of negotiation about condom use, especially by females 24 .…”
Section: Discussionmentioning
confidence: 58%
“…15 Determining which AGYW in SSA meet these definitions is challenging, yet important. 10,16 Much of the analysis-to-date has been conducted in South Africa among trial participants, 17-19 and understanding regional variation is critical.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Reconciling perceived risk, real-life behaviors, and validated risk indices is essential to effectively implement preventive measures such as PrEP. [20][21][22][23] Throughout the course of biomedicine, this reconciliation has often been achieved through the development of objective risk calculators. Incidence of cardiovascular disease and osteoporosis, for example, have been drastically reduced through the use of Framingham and DXA scores, respectively.…”
Section: Introductionmentioning
confidence: 99%